2007
DOI: 10.1007/s10681-007-9453-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and partial resistance to Phytophthora sojae in early maturity group soybean plant introductions

Abstract: Phytophthora sojae, an important yield limiting pathogen of soybean, causes seed, seedling, root, and stem rots. Losses caused by P. sojae can be controlled by both major gene and partial resistance. Early maturity group (MG) soybeans are an increasingly important crop in northwestern Minnesota and eastern North Dakota. Early MG plant introductions (PIs) from the USDA Soybean Germplasm Collection and early MG public and private cultivars were evaluated for resistance and partial resistance to P. sojae. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…However, partial resistance to P. sojae is reportedly expressed in the roots of cultivars with high levels of resistance (i.e., limited root rot and the absence of stem rot) ( Dorrance et al, 2007 ; Mideros et al, 2007 ; Schmitthenner, 1985 ; Tooley and Grau, 1984 ). The partial resistance expression site in the current study might be inconsistent with that of several other studies that assessed root damage ( Abeysekara et al, 2016 ; Burnham et al, 2003 ; Jia and Kurle, 2008 ; Lee et al, 2013a , 2013b ; McBlain et al, 1991 ; Schneider et al, 2016 ; Stewart and Robertson, 2012 ; Tucker et al, 2010 ; Wu et al, 2011 ). This discrepancy was likely because our evaluation was based on the damping-off elicited by the severe infection around the lower hypocotyl and not root damage.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…However, partial resistance to P. sojae is reportedly expressed in the roots of cultivars with high levels of resistance (i.e., limited root rot and the absence of stem rot) ( Dorrance et al, 2007 ; Mideros et al, 2007 ; Schmitthenner, 1985 ; Tooley and Grau, 1984 ). The partial resistance expression site in the current study might be inconsistent with that of several other studies that assessed root damage ( Abeysekara et al, 2016 ; Burnham et al, 2003 ; Jia and Kurle, 2008 ; Lee et al, 2013a , 2013b ; McBlain et al, 1991 ; Schneider et al, 2016 ; Stewart and Robertson, 2012 ; Tucker et al, 2010 ; Wu et al, 2011 ). This discrepancy was likely because our evaluation was based on the damping-off elicited by the severe infection around the lower hypocotyl and not root damage.…”
Section: Discussioncontrasting
confidence: 88%
“…Unlike Rps -mediated resistance, this incomplete resistance leads to different levels of susceptibility/resistance among cultivars and can be evaluated based on decreased infection or colonization efficiency, the development of smaller lesions, and the production of fewer oospores in infected plant tissue ( Dorrance, 2018 ; Mideros et al, 2007 ). In the US, soybean germplasm exhibiting various levels of partial resistance has been identified by screening the plant introduction series of the soybean germplasm collection belonging to the US Department of Agriculture ( Dorrance and Schmitthenner, 2000 ; Jia and Kurle, 2008 ; Schneider et al, 2016 ). Several quantitative trait loci have been detected ( Abeysekara et al, 2016 ; Burnham et al, 2003 ; Lee et al, 2013a , 2013b ; Schneider et al, 2016 ; Tucker et al, 2010 ; Wu et al, 2011 ).…”
mentioning
confidence: 99%
“…ÔWilliamsÕ) with known partial resistance characteristics were included as controls for comparison. ÔConradÕ was considered to have a high level of partial resistance to P. sojae, whereas ÔWilliamsÕ was a moderately susceptible cultivar (low level of partial resistance) (Burnham et al 2003, Jia andJames 2007). The level of partial resistance of ÔConradÕ, ÔWilliamsÕ, Su88-M21 (high level of partial resistance), Xinyixiaoheidou (low level of partial resistance) and RIL lines was determined according to the average lesion lengths measured from the slant board assays as described below, respectively.…”
Section: Plant Materialmentioning
confidence: 99%
“…Jia and Kurle (2007) reported that 3-, 5-, 7-, and 10-day-old P. sojae grown on V8 juice agar medium were used to inoculate soybean lines at the same growth stage, and no significant difference was found in plant reaction when equal amounts of the inoculum slurry were used. In this study, we used mycelium of 7-day-old cultures grown on LBA instead of oospores to inoculate hypocotyls and roots of seedlings.…”
Section: Discussionmentioning
confidence: 99%